CHRISTIANITY: A SURVEY OF DEVELOPMENT IN THE SECOND MILLENNIUM - Thonippara, Francis (Journal of Dharma, 2001)
The history of the Christian religion in the second millennium is very complex. A journey through the ten centuries reveals the ups and downs and the change in attitudes of the Christian world. When the second millennium began Christianity was mostly a European religion and a religion of the Eastern part of the former Roman Empire, Persia and Armenia. Except in the South West Coast of India, the Malabar Coast, and in China, Christianity was not known to the rest of Asia. By the end of the millennium, Christianity emerged as the largest religion in the world making her presence in the whole known world.